(untitled) (International Journal of Environmental Sciences, 2025)
Background: The main human pathogen that causes a variety of diseases is Staphylococcus aureus. The increasing prevalence of antibiotic-resistant bacteria may cause complications in addressing bacterial infections. Due to its extensive array of antibacterial and antibiofilm properties, the human peptide LL-37 is being considered as a potential substitute for conventional antibiotics. The objective of this research was to identify genes involved in the development of biofilms, and to assess the effectiveness of LL-37 in combating the resistant Staphylococcus aureus that are found in clinical samples, the purpose of this research was to assess the effectiveness of the compound as a biofilm inhibitor. Methods: Through biochemical analyses, selective media, VITEK-2, and molecular verification, 190 clinical samples were gathered from hospitals in Baghdad and analyzed for S. aureus. Identifying the increase of biofilms using the microtiter plate method. The PCR was employed to identify genes associated with biofilm formation (icaA and rbf). The lowest concentration of LL-37 that inhibited the growth of the bacterium was obtained by a microdilution method. The efficacy of LL-37 against biofilms was evaluated with a reader that employs ELISA and a stain that is composed of crystal violet. Result: 44 of the aislates were identified as S. aureus. All of the aislates developed biofilms, 17 of which were successful and 7 of which were MDR. Biofilm genes were employed to identify the icaA gene in 6 different isolates, while the rbf gene was encountered in all of them. The antibacterial activity of LL-37 was considered strong, with the MIC value of 62.5-250 μg/ml being demonstrated. Our results demonstrated a significant alteration to their capacity to form biofilms, as the aislates became less effective at forming biofilms, following the treatment of the antimicrobial peptide LL-37. In the treated strains, the formation of biofilms was markedly reduced. Conclusion: When compared to multiple-drug resistant S. aureus, LL-37 demonstrated a significant inhibitory effect and an anti-inflammatory capacity. These findings indicate that it could be a viable alternative to treat infections caused by MSAs. Its practical applications and mechanisms of action should be studied in greater detail.